INTERAKSI SOSIAL ANTAR PENGURUS ORGANISASI HIMPUNAN MAHASISWA PENDIDIKAN LUAR SEKOLAH (HIMA PLUS) PERIODE 2017-2018 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Nur Aseha; Titi Maemunaty; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the social interaction among the organizers of Overseas School Student Association (Hima Plus) organization period 2017-2018 Faculty of Teacher Training and Education University of Riau. This research uses descriptive method with quantitative approach. The sample in this study amounted to 50 people, the organizers of the Association of Students of Out of School Education (Hima Plus) period 2017-2018 with the technique of sampling saturated (total). Data collection techniques using questionnaires. Analysis data technique using SPSS program and percentage calculation. The results of this study indicate that the Out-of-School Student Association (Hima Plus) period 2017-2018 Faculty of Teacher Training and Education University of Riau in running activities and work programs for high cooperation among fellow administrators. Furthermore, in running the work program among fellow administrators there is also a high competition among administrators, this competition arises because of the desire of each board to get a role and position within the organization management. In addition there is competition within the organization of Out-of-School Education Student Association (Hima Plus) period 2017-2018 there is also a conflict, especially social class disagreement because of the desire to win alone. To reduce this conflict should be the attitude of tolerance and mutual respect between the board in order to achieve the goals of the organization. Key Words: Social Interaction, Out-of-School Student Association (Hima Plus) period 2017-2018